Change of Direction Ability Performance in Cerebral Palsy Football Players According to Functional Profiles - Reina, Raúl; Sarabia, Jose M.; Yanci, Javier; García-Vaquero, María P.; Campayo-Piernas, María (Frontiers in Physiology, 2016)
The aims of the present study were to evaluate the validity and reliability of the two different change of direction ability (CODA) tests in elite football players with cerebral palsy (CP) and to analyse the differences in performance of this ability between current functional classes (FT) and controls. The sample consisted of 96 international cerebral palsy football players (FPCP) and 37 football players. Participants were divided into four different groups according to the International Federation of Cerebral Palsy Football (IFCPF) classes and a control group (CG): FT5 (n = 8); FT6 (n = 12); FT7 (n = 62); FT8 (n = 14); and CG (n = 37). The reproducibility of Modified Agility Test (MAT) and Illinois Agility Test (IAT) (ICC = 0.82–0.95, SEM = 2.5–5.8%) showed excellent to good values. In two CODA tests, CG performed faster scores compared with FPCP classes (p < 0.01, d = 1.76–3.26). In IAT, FT8 class comparisons regarding the other classes were: FT5 (p = 0.047, d = 1.05), FT6 (p = 0.055, d = 1.19), and FT7 (p = 0.396, d = 0.56). With regard to MAT, FT8 class was also compared with FT5 (p = 0.006, d = 1.30), FT6 (p = 0.061, d = 0.93), and FT7 (p = 0.033, d = 1.01). No significant differences have been found between FT5, FT6, and FT7 classes. According to these results, IAT and MAT could be useful and reliable and valid tests to analyse CODA in FPCP. Each test (IAT and MAT) could be applied considering the cut point that classifiers need to make a decision about the FT8 class and the other FT classes (FT5, FT6, and FT7).